Measuring Organic Matter in Everglades Wetlands and the Everglades Agricultural Area - Alan L. Wright; Edward A. Hanlon (EDIS)
SL-285, a 5-page illustrated fact sheet by Alan L. Wright and Edward A. Hanlon, recommends for growers, managers, and researchers the new and simple Loss-On-Ignition (LOI) test for determining the organic matter content of soils. Includes additional sources of information. Published by the UF Department of Soil and Water Sciences, April 2009.